The Reflectometer: A Novel Tool for Capturing the Quality of Students’ Learning Experiences in Health Care Education, and Beyond - Fjellaksel, Richard; Dassler, Tim; Dahl, Tove Irene (Radiography Open, 2025)
This paper introduces the Reflectometer, a novel tool designed to systematically capture and assess the quality and intensity of students’ learning experiences. Grounded in theories of experiential and transformative learning, the Reflectometer enables the identification of Key Learning Moments (KLMs), including both Dislocatory Moments (DMs) and Key Memorable Events (KMEs), and supports the analysis of reflective processes such as double-loop learning. The tool combines visual and qualitative data to provide a multidimensional account of when and how learning occurs. We tested the Reflectometer in two contrasting educational contexts – radiography education and avalanche safety training – demonstrating its adaptability, utility, and capacity to reveal both expected and unexpected learning dynamics. The Reflectometer not only offers students a structured medium for reflection but also provides educators with valuable insights into students’ learning experiences, thereby enabling two-way learning. Our findings suggest that the Reflectometer provides a promising method for stimulating reflective practice and assessing the impact of pedagogical strategies across diverse learning environments.